(untitled) (Comparative & International Education Series, 2021)
Globalization, international programs, and international student and scholar mobility have resulted in a changing demographic in classrooms across European universities. This diversity poses opportunities and challenges for instruction as faculty seek to engage in effective teaching. Funded by the U.S.-Italy Fulbright Commission, the authors discuss the analysis and implications from a large, nation-wide study on faculty perspectives about teaching international graduate students in Italy. Instructors from five universities participated and provided perspectives on the attitudes and values that instructors in international programs have for teaching international student populations. These perspectives offer insights for future professional development needs for continued learning and growth for instructors in these roles.